Factors Affecting Stunting Among Toddlers Aged 24-25 Months - Ervina, Anis; Zulmi, Daini; Ariesta, Rita; ., Roslina; ., Aminah; Aridawarni, Yulica (KnE Social Sciences, 2023)
Toddler growth disorders with indicators of relatively short heights are usually called stunting. This study aims to determine factors related to stunting in toddlers aged 24-59 months in Tambakbaya Village, Cibadak Public Health Center. A case-control method was used for this research. The population in this study were all mothers who had toddlers aged 24-59 months in Tambakbaya Village. The sample used was 44 mothers, where the case and control groups had a ratio of 1:1. The Chi-square test was used to analyze the data. Statistical analysis found no association between maternal nutrition during pregnancy and child growth (height/weight) at 24–59 months (p = 0.472), birth weight (p = 0.488), birth length (p = 0.698), vaccination status (p = 0.412), growth (height/weight) at 24–59 months (p = 0.698). However, this study showed a potential risk of stunting as shown by the odds ratio (OR) value. This result was due to the high awareness of participation in the Integrated Health Center every month, which can detect stunting cases easily and quickly. This condition affects health workers’ immediate action to prevent and address the issues by providing additional nutrition. Maternal nutrition needs to be considered through monitoring the mother’s nutritional status during pregnancy through ANC and monitoring and improving child nutrition after birth, namely the first 1000 days of life. Keywords: birth length, birth weight stunting, immunization, nutrition